Indonesian discourse particles in conversations and written text - Karàj, David-M (UI Scholars Hub, 2021)
The aim of the present paper is an analysis of four most frequent Colloquial Indonesian discourse particles (lho, kok, sih and dong) and the comparison of their occurrences in both spontaneous spoken conversations as well as in written texts (articles from a youth magazine). The author's motivation for choosing the terms discourse particles (instead of for example pragmatic particles) is explained and a new definition of the phenomenon is proposed. First the particles' meanings as given in various dictionaries are presented, it is followed by examples from spontaneous conversations. Next, examples from written text are given, followed by an analysis of possible differences and similarities in meaning. Finally, the possible particles' meanings are presented as sample sentences using the explication method. In the Conclusions, the author makes an attempt at answering the question whether the discourse particles in Colloquial Indonesian can be considered to be a separate word class.